Discursive angles on the relationship in psychotherapy - Muntigl, Peter; Scarvaglieri, Claudio (Frontiers in Psychology, 2023)
Research on the psychotherapy relationship has been dominated by quantitative-statistical paradigms that focus on relationship elements and their (evidence-based) effectiveness regarding the psychotherapy process. In this mini review, we complement this existing line of research with a discursive-interactional view that focuses on how the relationship is accomplished between therapists and clients. Our review highlights some of the main studies that use micro-analytic, interactional methods to explore relationship construction of the following elements: the alliance (affiliation), cooperation (alignment), empathy and rupture-resolution. We not only provide a summary of important discursive work that provides a unique lens on how the relationship may be established and maintained, but also suggest that this kind of micro-analytic approach can offer more nuanced conceptualizations of the relationship by showing how different elements work together in a synergistic manner.